Research of Spinal Cord Stimulation and its Applications - Ren, He (Transactions on Computer Science and Intelligent Systems Research, 2024)
Spinal cord stimulation (SCS) is a neurostimulation technique that has emerged as a promising therapeutic option for the management of chronic pain and other neurological disorders. An SCS consists of a implantable pulse generator (IPG) connected to a lead with a cathode (negative electrode) and an anode (positive electrode). The cathode and anode create an electrical field within the biological tissue that can depolarize the target nerves. In order to achieve the best results, the stimulation parameters in spinal cord stimulation (SCS) are carefully adjusted. The standard variables used in SCS include frequency, pulse width, and amplitude. In traditional SCS therapies, the primary goal has been to alleviate pain by replacing it with a tingling or paresthesia sensation. This approach involves mapping the stimulation to the specific region of pain to effectively mask the sensation of discomfort. In recent years, there have been significant advancements in the field of stimulation frequencies, particularly in the use of high-frequency SCS (at 10,000 Hz) and burst SCS. High-frequency 10 SCS (HF10) is a groundbreaking advancement in the field of spinal cord stimulation (SCS) technologies. This innovative approach involves delivering a unique waveform at 10,000 Hz, which operates below the threshold for sensory perception, thereby providing effective pain relief without causing any paresthesia or abnormal sensations. Another exciting development is burst SCS, which involves delivering bursts of closely spaced electrical pulses instead of continuous stimulation.